Degradability of biodegradable plastic films and its mulching effects on soil temperature and maize yield in northeastern China - Zhang, Wangwang; Wang, Lihong; Zhou, Jiaqi; Zhu, Kunlun; Sun, Shijun (International Journal of Agricultural and Biological Engineering, 2020)
Plastic film is an important resource in agricultural production, but it takes hundreds of years to degrade completely in natural environment. The large-scale use of plastic film will inevitably lead to serious environmental pollution. One way to solve the problem is to develop a substitutable mulching film, such as a biodegradable ﬁlm that can ultimately be decomposed to water, carbon dioxide, and soil organic matter by micro-organisms. In this study, a 2-year experiment was conducted to determine the degradation properties of a biodegradable plastic film, including degradation rate, surface microstructure, tensile strength and elongation at break, and the effects of different mulching treatments on soil temperature and maize yield. The mulching experiment was conducted with three different biodegradable plastic films with different degradation rates, using a common plastic film and a non-mulched treatment as control. With the addition of the additives for degradation in the biodegradable plastic films, the degradation rates increased significantly, which were 7.2%-17.8% in 2017 and 18.1%-35.2% in 2018 after maize harvesting. However, the degradation occurred mainly on the ridge side. The decrease in tensile strength and elongation was proportional to the degradation rate of the degradable film. The SEM results indicated that the surface microstructures of the biodegradable films were loose and heterogeneous after maize harvesting. Biodegradable plastic film mulching increased the soil temperature at soil depths of 5 cm, 15 cm, and 25 cm, over the maize’s entire growth period, by 3.1°C-3.2°C in 2017 and 1.2°C-2.1°C in 2018 compared with the non-mulched treatment. The biodegradable plastic film increased the maize yield by 10.4%-14.3% in 2017 and 11.6%-24.7% in 2018. The soil temperature and maize yield increases were statistically significant; however, with respect to maize qualities, there were no statistically significant increases among the five treatments. This study shows that biodegradable plastic film can be used as a substitute for common plastic film. However, the ingredients in biodegradable plastic films should be improved further to ensure that they can be degraded completely after crop harvest.Keywords: biodegradable plastic film, film mulching, degradation properties, soil temperature, maize yieldDOI: 10.25165/j.ijabe.20201302.5360Citation: Zhang W W, Wang L H, Zhou J Q, Zhu K L, Sun S J. Degradability of biodegradable plastic films and its mulching effects on soil temperature and maize yield in northeastern China. Int J Agric & Biol Eng, 2020; 13(2): 146–153.